Low bound on a magnetic field strength in the hot universe - Elizalde, E.; Skalozub, V. (Вопросы атомной науки и техники, 2012)
It is assumed that the intergalactic magnetic fields were spontaneously generated in the early Universe due to vacuum polarization of non-Abelian gauge fields at high temperature T. Here, a procedure to estimate the field strengths B(T) at different T is developed and the value of B(Tew) ~ 10⁻¹⁴ G, at the electroweak phase transition temperature, is derived by taking into consideration the present intergalactic magnetic field strength B0 ~ 10⁻¹⁵ G.